2020
DOI: 10.3390/ijms21207452
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Glutamatergic Neurotransmission in Alzheimer’s Disease: From Pathophysiology to Pharmacotherapy

Abstract: Alzheimer’s disease (AD) is an age-related dementia and neurodegenerative disorder, characterized by Aβ and tau protein deposition impairing learning, memory and suppressing synaptic plasticity of neurons. Increasing evidence suggests that there is a link between the glucose and glutamate alterations with age that down-regulates glucose utilization reducing glutamate levels in AD patients. Deviations in brain energy metabolism reinforce the development of AD by hampering glutamate levels in the brain. Glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 232 publications
(254 reference statements)
2
68
0
Order By: Relevance
“…It is also a substrate for glutathione synthesis, basic building block for proteins, and a potential inhibitory agent for inflammatory cytokine release [ 52 ]. An increased of L-glutamine in the brain of BChE KO mice in this study is consistent with our previous publication in which BChE inhibition restored the decreased of L-glutamine in Aβ-42-induced astrocytes [ 30 ], and the glutamate–glutamine cycle has a pivotal role in the etiology of AD [ 53 ]. Studies also have found that the increase of L-glutamine and N-acetyl aspartic acid can reduce the risk of depression [ 50 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is also a substrate for glutathione synthesis, basic building block for proteins, and a potential inhibitory agent for inflammatory cytokine release [ 52 ]. An increased of L-glutamine in the brain of BChE KO mice in this study is consistent with our previous publication in which BChE inhibition restored the decreased of L-glutamine in Aβ-42-induced astrocytes [ 30 ], and the glutamate–glutamine cycle has a pivotal role in the etiology of AD [ 53 ]. Studies also have found that the increase of L-glutamine and N-acetyl aspartic acid can reduce the risk of depression [ 50 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Age-Related Disturbances of Glutamatergic Signaling in the Pathogenesis of AD and PD Glutamate seems to play a pivotal role in the etiology of AD and PD, because of its abundance in brain tissue and, in part, because it is at the crossroads of multiple metabolic pathways. It has been shown that if the balance of glutamate turnover is disrupted, the perturbation of glutamate neurotransmission has severe consequences, leading to the onset of neurodegenerative diseases (reviewed by Bukke et al, 2020;Iovino et al, 2020;Wang J. et al, 2020). Understanding the role of the glutamatergic system in the pathophysiology of AD and PD may allow the development of improved therapeutics for these neurodegenerative disorders.…”
Section: Expression Of Glutamatergic Receptorsmentioning
confidence: 99%
“…Depending on the frequency of the synaptic activity, AMPARs are either inserted or removed from synapses, resulting in the potentiation or depression of synaptic transmission, respectively [ 120 ]. One of the most well-studied pathophysiological phenomena that involves AMPARs is their oligomer-induced internalization [ 163 ], for which different molecular mechanisms have been hypothesized [ 178 ]. For instance, AMPAR’s GluR3 subunit was found to be involved in receptor internalization in the early phases of AD, leading to the onset of memory deficits in a mouse model of disease [ 179 ].…”
Section: Impairment Of Synaptic Excitability Transmission and Plasticitymentioning
confidence: 99%
“…Notably, seizures may not only be seen as a consequence of neurodegeneration induced by oligomers accumulation, but epileptic discharges may serve themselves as a facilitating factor for amyloid deposition, since amyloid burden was found to be significantly increased in a population of adult patients with childhood-onset epilepsy [ 220 ]. On the other side of the E/I scale, glutamate receptors’ dysfunctions have been associated with oligomer-induced alterations of neurotransmission [ 178 , 221 ]. The modulation of NMDAR by memantine has been reported to restore LTP in the DG of mice expressing the Swedish-Indiana APP mutation [ 222 ], and this effect was due to a normalization of the NMDA to AMPA ratio.…”
Section: Oligomers and Alteration Of Excitatory/inhibitory (E/i) Neurotransmissionmentioning
confidence: 99%